Smart farm control gate / Hasnizawati Shahrudin … [et al.] - Shahrudin, Hasnizawati; Ghazali, Mohd Zaki; Md Saidi, Raihana; Zainol, Zarina; Adnan, Rosanita (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This system was built using Parallax Basic Stamp Microcontroller to overcome problem with trespassers in farms. Farms without good fence system may expose to crops products lost. Therefore, security and identification system to enter the farm should be emphasized since it also contributes to the reduction of the crime rates in the farm area. Apart from that, the system may help farmers to increase crop yields in order to boost economic income in the country. The system could be easily implemented by statutory bodies, due to its low cost.